3D Whole Heart Imaging for Congenital Heart Disease - Greil, Gerald; Tandon, Animesh (Aashoo); Silva Vieira, Miguel; Hussain, Tarique (Frontiers in Pediatrics, 2017)
Three-dimensional (3D) whole heart techniques form a cornerstone in cardiovascular magnetic resonance (CMR) imaging of congenital heart disease (CHD). It offers significant advantages over other CHD imaging modalities and techniques: no ionizing radiation; ability to be run free-breathing; ECG gated dual-phase imaging for accurate measurements and tissue properties estimation; and higher signal-to-noise ratio and isotropic voxel resolution for multi-planar reformatting assessment. However, there are limitations, such as potentially long acquisition times with image quality degradation. Recent advances in and current applications of 3D whole heart imaging in CHD are detailed, as well as future directions.